The UNEJ KKN Program 'Smart Kids': Local Food Innovation In Stunting Mitigation Through Moringa And Soybean Husk (Glycine Max) Products: Program KKN UNEJ 'Smart Kids' : Inovasi Pangan Lokal Dalam Mitigasi Stunting Melalui Produk Kelor Dan Kulit Ari Kedelai (Glycine Max) (AgroNurse Kesehatan : Jurnal Pengabdian Masyarakat, 2024)
Stunting is one of the significant chronic nutritional issues in Indonesia, especially among  young children. Data shows that although the prevalence of stunting has decreased, it remains high, including in Lumajang Regency, with a prevalence rate of 23.8%. Sawaran Lor village has local potential in the form of nutrient-rich moringa leaves, but their utilization has not been optimal. Another local potential, soybean hull waste from the tempeh industry, which is usually only used as animal feed, contains nutrients that can be utilized as functional food. The "SMART KIDS" program (Stunting Mitigation and Recovery through Kelor Pudding and Soybean Cookies) was initiated by KKN 242 Universitas Jember as an effort to combat stunting through local food innovation. This program involved training posyandu cadres and mothers of young children in Sawaran Lor village to process moringa leaves into pudding and soybean hull waste into high-fiber cookies. The results of the activities showed an increase in participants' knowledge and skills in processing local food resources to support stunting prevention and improve the local economy.